Investigation of the effect of life skill training on attitude towards substance abuse in sirjan city high school students - Morteza Abdollahpour; Mahmood Golzari (Drug Control Headquarters, Research and Education Office, 2009)
Objectives: The present research investigated the effect of life skills training on attitude towards substance abuse in sirjan city high school students. Methods:The sample of this research includes 40 boy students (20 experimental, 20 control) from one high school by using random selection sampling method. They pre tested and then choose experimental group by the scores of pretest. Experimental group have been thought life skills along one month in 8 sessions, but the control group received no variable. Finding:At the end, both of them were post tested by using addiction attitude measuring scale (form B). Discussion: The data were analyzed by applying covariance test and t test. The result indicated that life skills training are effective in changing student's attitudes towards substance abuse.